2017
DOI: 10.1111/anu.12597
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chinese herbal medicines mixture on growth performance digestive enzyme activity immune response of juvenile Japanese seabass,Lateolabrax japonicus

Abstract: A single factorial experiment was conducted to investigate the effects of Chinese herbal medicines mixture (CHMM) on growth performance, digestive enzyme activity and immune response of Japanese seabass, Lateolabrax japonicus (initial weight 5.01 ± 0.32 g). The fish were fed diets containing six levels of CHMM (0, 4, 8, 12, 16 and 20 g/kg) for 4 weeks. The results showed that the weight gain rate and specific growth rate (SGR) enhanced significantly in fish fed diet containing 8 g/kg CHMM (p < .05), while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 76 publications
5
36
0
Order By: Relevance
“…Medicinal plants have been confirmed to promote aquatic animals growth performance, immunity and digestive enzyme activity (Abarike et al, ; Citarasu, ; Reverter, Bontemps, Lecchini, Banaigs, & Sasal, ; Wang et al, ). Several researchers have reported that garlic can improve growth performance of aquatic animals, such as sterlet sturgeon ( Acipenser ruthenus ), caspian roach ( Rutilus rutilus ), brown trout ( Salmo caspius ) and rainbow trout ( Oncorhynchus mykiss ) (Büyükdeveci, Balcazar, Demirkale, & Dikel, ; Ghehdarijani, Hajimoradloo, Ghorbani, & Roohi, ; Lee et al, ; Zaefarian, Yeganeh, & Adhami, ), and all of their results showed a similar trend garlic supplementation at 10 g/kg can significantly improve fish growth performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medicinal plants have been confirmed to promote aquatic animals growth performance, immunity and digestive enzyme activity (Abarike et al, ; Citarasu, ; Reverter, Bontemps, Lecchini, Banaigs, & Sasal, ; Wang et al, ). Several researchers have reported that garlic can improve growth performance of aquatic animals, such as sterlet sturgeon ( Acipenser ruthenus ), caspian roach ( Rutilus rutilus ), brown trout ( Salmo caspius ) and rainbow trout ( Oncorhynchus mykiss ) (Büyükdeveci, Balcazar, Demirkale, & Dikel, ; Ghehdarijani, Hajimoradloo, Ghorbani, & Roohi, ; Lee et al, ; Zaefarian, Yeganeh, & Adhami, ), and all of their results showed a similar trend garlic supplementation at 10 g/kg can significantly improve fish growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the results showed garlic had a significant influence in the content of TP and activity of LPS and trypsin, and the highest values among all the groups were found at around 10 g/kg diet. Medicinal plants have functions on increasing fish intestinal digestion (Wang et al, ). Researches reported that garlic contains allicin, which can improve digestion and enhance the utilization of energy because of its beneficial effects on the intestinal microflora (Büyükdeveci et al, ; Lee et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum lysozyme (LZM) activity was measured based on the lysis of Micrococcus luteus according to the method of Ellis (Wirth, Wolf, Wirth, & Wolf, ). The total protein (TP), alkaline phosphatase (AKP) and total superoxide dismutase (T‐SOD) activities in serum were determined using a reagent kit (Jiancheng) as described previously (Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Japanese seabass were fed with the control diet for 2 weeks in circulating filter barrel, for them to adapt to the new diet and environmental conditions before starting the experiment. At the beginning of the experiment, the Japanese seabass were treated with feed deprivation for 24 hr, and weighed after being anaesthetized with eugenol (1:10,000) (Wang et al, ). 360 Japanese seabass with an average weight of (27.09 ± 0.08) g were selected and randomly assigned into six groups; each group repeated the experiment 3 times and 20 fishes were stocked each time.…”
Section: Methodsmentioning
confidence: 99%